Building a Social Protection Index (SPI) for Nepal - Sharma, Suman Kumari (Economic Journal of Nepal, 2005)
The main objectives of the present paper are to outline the existing social protection interventions in Nepal, to highlight the relationship between poverty, vulnerability and the need for social protection interventions, and to compute a set of sub-indicators that are essential in building an internationally comparable social protection index for Nepal. This paper, first of all, briefly outlines the existing social protection interventions in Nepal that are aimed at reducing poverty and vulnerability. Next, it highlights some conceptual framework of the relationship between poverty, vulnerability and social protection interventions. Next, beginning with some initial thoughts on building a Social Protection Index, this paper computes a set of sub-indicators that are considered essential for building an internationally comparable social protection index (SPI) for Nepal. Economic Journal of Nepal Vol.28(3) 2005 pp.149-168